Honokiol, a Polyphenol Natural Compound, Attenuates Cisplatin-Induced Acute Cytotoxicity in Renal Epithelial Cells Through Cellular Oxidative Stress and Cytoskeleton Modulations - Wang, Tse-En J.; Liu, Hung-Ting; Lai, Yu-Hua; Jan, Tong-Rong; Nomura, Naohiro; Chang, Hui-Wen; Chou, Chi-Chung; Lee, Ya-Jane; Tsai, Pei-Shiue J. (Frontiers in Pharmacology, 2018)
Cisplatin is a potent anti-cancer drug that has been widely used in the treatment of various cancers; however, cisplatin administration results in severe nephrotoxicity and impedes its clinical applications. In this study, we showed that honokiol, a polyphenol constituent extracted from Magnolia officinalis exhibited a short-term protective effect against cisplatin-induced damages in renal epithelial cells in vitro. The protective effects of honokiol were resulted from the combination of (1) reduced cellular oxidative stress ranging from 53%-32% reduction during a 24-hour incubation, (2) the maintenance of cellular antioxidant capacity and (3) the stabilization of cytoskeletal structure of the kidney epithelial cells. By promoting the polymerization of actin (1.6-fold increase) and tubulin (1.8-fold increase) cytoskeleton, honokiol not only maintained epithelial cell morphology, but also stabilized cellular localizations of tight junction protein Occludin and adhesion junction protein E-Cadherin. With stabilized junction protein complexes and structural polymerized cytoskeleton network, honokiol preserved epithelial cell polarity and morphology and thus reduced cisplatin-induced cell disruption and damages. Our data demonstrated for the first time that honokiol could counteract with cisplatin-induced damages in renal epithelial cells in vitro, future in vivo studies would further validate the potential clinical application of honokiol in cisplatin-based cancer treatments with reduced nephrotoxicity.